Closure of Midline Diastema Following Frenectomy with M-Spring: A Case Report - Shailesh Kulkarni; Pratik Ghule; Amit Handa; Himanshu Srivastava; Aditi Sarda (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Midline diastema, a gap between the maxillary central incisors, is a commonly seen orthodontic anomaly. Persistent diastemas which occur naturally in the younger age group can happen in adults too. It can cause psychological distress, speech difficulty, under functional concern. If the individual has a high or thick labial frenum that prevented the natural movement of the teeth, one might expect a recurrence after orthodontic treatment. An association of orthodontic appliances and frenectomy would serve as an efficient solution to the aesthetic and functional nature of the problem. Case Presentation: A midline diastema of 2.5 mm was reported in the 22-year-old female patient. Clinical examination revealed a thick, low-attaching labial frenum which was the reason for the diastema. A custom-made M Spring appliance was used to apply controlled gentle forces for the desired mesial movement of the central incisors. After a period of six weeks, the space was successfully closed with optimal incisor positioning, and a frenectomy was done to eliminate the high frenum attachment. Following the frenectomy and subsequent healing of the soft tissue, a bonded fixed retainer was installed on the palatal surfaces of the central incisors. Conclusion: The midline diastema was treated with the M Spring appliance followed by the frenectomy which is a conservative, effective, and least invasive treatment. The custom M Spring allows controlled space closure with frenectomy removal of the etiological factor preventing any chances of relapse. This case underlines the needs for consideration of mechanical and soft tissue factors for permanent and aesthetic results.